Nilai Perusahaan yang dipengaruh oleh Efisiensi Operasional, Kepemilikan Manajerial dan Intellectual Capital - Roswanti, Andini; Oktavianna, Rakhmawati; Rini, Ratih Setyo (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to analyze and prove empirically the effect of operational efficiency, managerial ownership, and intellectual capital on firm value. This type of research is associative quantitative using secondary data taken from the Indonesia Stock Exchange website and company websites. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample selection procedure in this study uses as many as 42 company data that match the criteria. The data analysis technique used is multiple linear regression analysis using E-views 10. The results of this study indicate that operational efficiency, managerial ownership, and intellectual capital simultaneously affect firm value. Partially, operational efficiency influences firm value, while managerial ownership and intellectual capital has no effect on firm value.